SEBARAN DAERAH RENTAN PENYAKIT DBD MENURUT KEADAAN IKLIM MAUPUN NON IKLIM(DISTRIBUTION OF VULNERABLE REGION OF DENGUE FEVER DISEASE BASED ON CLIMATE AND NON-CLIMATE CONDITION) - Rini Hidayati; Rizaldi Boer; Yonny Koesmaryono; Upik Kesumawati; Sjafrida Manuwoto (Agromet, 2008)
This research was aimed to investigate distribution of vulnerable region of dengue fever disease based on climate condition and population density in Indonesia. Climate condition, population density and vulnerability of district level were defined in the form of ordinal variable. The Koppen classification was used to proxy the climate condition. The population density was used to categorize the district level into small, medium and big cities. Regional vulnerability level was developed by using the values of IR and the 3-year consecutive incidence. The result of analysis using the frequency of incidence clarified that the population density and climate pattern influences the vulnerable level of the district. The big cities whose climate type are of Am (annual rainfall more than 1000 mm) and dry season is not extreme are the riskiest vulnerable region. On the contrary, the small cities whose dry season is not clear have high probability to be the safest region.